2017
DOI: 10.1016/j.trc.2017.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Turning meter transactions data into occupancy and payment behavioral information for on-street parking

Abstract: Over 95% of on-street paid parking stalls are managed by parking meters or kiosks. By analyzing meter transactions data, this paper provides a methodology to estimate on-street timevarying parking occupancy and understand payment behavior in an effective and inexpensive way. We propose a probabilistic payment model to simulate individual payment and parking behavior for each parker. Aggregating the payment/parking of all transactions leads to timevarying occupancy estimation. Two data sets are used to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…Parkers are most likely to park in a block and purchase a ticket from any of the affiliated meters near this block. Locations of the 97 parking meters and centroids of the 39 street blocks are plotted in Fig 3. Previously, we have shown that true parking occupancies can be approximated using meter transaction data with a few days of occupancy ground truth collected manually (Yang and Qian, 2017). Since the main focus of this case study is evaluating the performance of the proposed model, we convert meter transactions to parking occupancies in a straight forward wa: we make the assumption that all vehicles start parking right after the payment is made and leave at the moment parking session expires, and there is no unpaid parking.…”
Section: Parking Meter Transactionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Parkers are most likely to park in a block and purchase a ticket from any of the affiliated meters near this block. Locations of the 97 parking meters and centroids of the 39 street blocks are plotted in Fig 3. Previously, we have shown that true parking occupancies can be approximated using meter transaction data with a few days of occupancy ground truth collected manually (Yang and Qian, 2017). Since the main focus of this case study is evaluating the performance of the proposed model, we convert meter transactions to parking occupancies in a straight forward wa: we make the assumption that all vehicles start parking right after the payment is made and leave at the moment parking session expires, and there is no unpaid parking.…”
Section: Parking Meter Transactionsmentioning
confidence: 99%
“…In the literature, most studies "estimate" parking occupancies at the current moment (Boyles et al, 2015;Yang and Qian, 2017;Alajali et al, 2017), as opposed to "predicting" (or "forecasting") parking occupancies in the near future. There are generally two ways to predict short-term parking occupancy: (1) Model individual drivers' stochastic arrival and departure behaviors in a microscopic manner (Caicedo et al, 2012;Boyles et al, 2015;Caliskan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research has observed, however, that transaction data can be used to estimate parking occupancy and, in consequence, used to estimate resource performance [Yang andQian, 2017, Dowling et al, 2017]. The distinction that occupancy below 100% results in congestion has recently been noted by [Millard-Ball et al, 2014] in their own analysis of the SFPark pilot study parallel to [Pierce and Shoup, 2013], however the authors of [Millard-Ball et al, 2014] view block-face parking as a Bernoulli random variable, between being full or not.…”
Section: Related Workmentioning
confidence: 99%